Efektifitas Latihan Stretching Terhadap Penurunan Nyeri Akibat Musculoskeletal Disorder (MSDs) Di Tempat Kerja - Dwi Purwantini; Febronia Norita Mariana; Angela Putri Karla Ruslani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Stretching exercise is a therapeutic exercise that aims to increase soft tissue extensibility. Stretching has a positive effect on musculoskeletal symptoms and reduces pain and can prevent work-related musculoskelatal injuries. This study aims to analyze the effect of stretching exercises on reducing pain due to musculoskeletal disorders (MSDs) in the workplace. This type of research is experimental research design with one group pre test-post test design. The research subjects were 30 employees at PT Naka Tujuh Gemilang. Subjects received stretching exercise intervention for 10-15 minutes which was done 2-3 times per week for 2 weeks. Subjects were measured the quality of pain with the Verbal Descriptor Scale (VDS) before and after stretching exercises. The research data shows that p = 0.00 Ho is rejected and Ha is accepted, so the hypothesis states that stretching exercises have an effect on decreasing VDS values. The conclusion of this study is that stretching exercises are effective in reducing pain due to musculoskeletal disorders (MSDs) in the workplace